Implementing integrated teaching method in standardized specialist training for rehabilitation physicians - Liao Chunhua; Wang Xiaoming; Wang Lin; Yang Shanru; Liu Rui (Guoji laonian yixue zazhi)
[Objective] To investigate the feasibility and benefits of implementing an integrated teaching model in the standardized training of rehabilitation medicine specialists. [Methods] A total of 80 trainees undergoing standardized training at Tangdu Hospital from January 2021 to June 2023 were randomly assigned to either an experimental group or a control group, with 40 trainees each. The experimental group utilized an integrated teaching model, whereas the control group followed the traditional teaching approach. Teaching effectiveness was assessed through various measures, including process assessment (clinical thinking training notes), multi-station clinical skills evaluations skill performance and annual theoretical assessment. [Results] The experimental group demonstratd significantly higher overall scores compared to the control group in theoretical knowledge, skill performance, multi-station clinical skills assessment and process evaluations, with the differences being statistically significant(P<0.05). [Conclusion] The integrated teaching model has proven to be valuable approach in the standardized training of rehabilitation medicine specialists at our hospital. This model enhances the the comprehensive quality and capabilities of trainees, offering a superior alternative to traditional teaching methods.